2003
DOI: 10.1128/ec.2.2.222-230.2003
|View full text |Cite
|
Sign up to set email alerts
|

Exportin 1 Mediates Nuclear Export of the Kinetoplastid Spliced Leader RNA

Abstract: The kinetoplastid protozoan spliced leader (SL) RNA is the common substrate pre-mRNA utilized in all trans-splicing reactions. Here we show by fluorescence in situ hybridization that the SL RNA is present in the cytoplasm of Leishmania tarentolae and Trypanosoma brucei. Treatment with the karyopherin-specific inhibitor leptomycin B was toxic to T. brucei and eliminated the cytoplasmic SL RNA, suggesting that cytoplasmic SL RNA was dependent on the nuclear exporter exportin 1 (XPO1). Ectopic expression of xpo1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
82
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 51 publications
(70 reference statements)
0
82
0
Order By: Relevance
“…It was initially proposed that since cap-4 formation is cotranscriptional, SL RNA assembly takes place in the nucleus (Mair et al 2000). Later it was suggested that XPO1, an export factor, may mediate the transport of the SL RNA from the nucleus to the cytoplasm, suggesting that at least part of the assembly process may occur in the cytoplasm (Zeiner et al 2003). The observation of large cytoplasmic SL RNA speckles (SL RNP-C) during Sm depletion supports the cytoplasmic assembly of SL RNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was initially proposed that since cap-4 formation is cotranscriptional, SL RNA assembly takes place in the nucleus (Mair et al 2000). Later it was suggested that XPO1, an export factor, may mediate the transport of the SL RNA from the nucleus to the cytoplasm, suggesting that at least part of the assembly process may occur in the cytoplasm (Zeiner et al 2003). The observation of large cytoplasmic SL RNA speckles (SL RNP-C) during Sm depletion supports the cytoplasmic assembly of SL RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently two distinct methyltransferases that carry out the 29-O9-methylations at positions +3 and +4 and +2 of the cap-4 were identified and localized to the nucleus (Arhin et al 2006a,b) . Despite the fact that many factors involved in SL RNA biogenesis are found within the nucleus, studies from recent years suggested that SL RNA biogenesis, nevertheless, involves a cytoplasmic phase (Mandelboim et al 2003;Zeiner et al 2003). It was suggested that export of SL RNA to the cytoplasm is mediated by XPO1 (Zeiner et al 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cap formation on the SL RNA proceeds in a 5Ј-3Ј direction, as indicated by experiments performed with permeable trypanosomes (Ullu and Tschudi 1995). It appears that at least part of the modifications occur cotranscriptionally, as shown in studies using permeable trypanosomes (Mair et al 2000) and that sequences within the SL RNA coding gene are required for obtaining the complete cap-4 structure (Ullu and Tschudi 1995;Zeiner et al 2003). However, it was recently shown that the cytoplasmic stage is necessary for SL RNA biogenesis (Zeiner et al 2003).…”
Section: Leishif4e-1 Binds M 7 Gtp and Cap-4mentioning
confidence: 99%
“…It appears that at least part of the modifications occur cotranscriptionally, as shown in studies using permeable trypanosomes (Mair et al 2000) and that sequences within the SL RNA coding gene are required for obtaining the complete cap-4 structure (Ullu and Tschudi 1995;Zeiner et al 2003). However, it was recently shown that the cytoplasmic stage is necessary for SL RNA biogenesis (Zeiner et al 2003). It was further suggested that U4 modification of the SL RNA most probably serves as a signal for transport of snRNPs between the nucleus and the cytoplasm (Mandelboim et al 2003).…”
Section: Leishif4e-1 Binds M 7 Gtp and Cap-4mentioning
confidence: 99%